(untitled) (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2019)
In Serbia, there are several categories of persons deprived of their liberty, which for the time while they are in a penal institution have certain rights and obligations. Thus, in penal institutions, the sentence of imprisonment, which was pronounced in the criminal, as well as in the misdemeanor procedure, is served. The penalty of juvenile imprisonment shall be executed in the penitentiary institution for juveniles. The educational measure of referral to a correctional home is executed in a Juvenile Correctional Facility in Krusevac. In penitentiary institutions is also executed the punishment of supletory prison, as also as detention. For all persons is a common, and that is that they are deprived of their liberty, and their treatment while deprived of their liberty differ. The subject of the author’s work is the work of persons deprived of their liberty, that is, their legal order in the Republic of Serbia. The aim of the work is to see how the legislator has regulated the working engagement of persons deprived of liberty, but also to see how the sub-legal acts further regulate this area. The current regulations governing the working engagement of persons deprived of their liberty will be critically analyzed.